Employee Development Strategy Innovation Towards a Sustainable Organization: A Systematic Review Using Bibliometric Methods (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study investigates innovative employee development strategies that drive the formation and sustainability of modern organizations. Employing a systematic review supported by bibliometric analysis, this research maps the intellectual structure, publication trends, and emerging themes within the intersection of employee development and organizational sustainability. Data were retrieved from leading academic databases and analyzed using bibliometric visualization tools to identify co-citation networks and keyword clusters. The findings indicate a significant shift toward innovation-oriented development approaches, emphasizing digital transformation, continuous learning, and sustainable human capital practices. Moreover, the study highlights the strategic importance of aligning employee development initiatives with long-term organizational goals and environmental sustainability. The results provide a comprehensive understanding of how innovation in employee development contributes to sustainable organizational performance and resilience in a dynamic global context.
Keywords: employee development; innovation; sustainability; bibliometric analysis; systematic review; human capital; organizational resilience